MASTERY OF FUNCTIONAL ANATOMY AND MEANINGFUL LEARNING IN INTRODUCTORY BIOMECHANICS - Belmont, Rachel Saraiva; Knudson, Duane; Lobo da Costa, Paula Hentschel; Lemos, Evelyse dos Santos (Revista Práxis, 2016)
Although there is a consensus that musculoskeletal anatomy is essential knowledge for learning biomechanical concepts, there are few studies that have documented the nature of this interdependence. A qualitative case study approach was used to identify how the applied knowledge of functional anatomy might influence meaningful learning of biomechanics. Thirteen physical education students enrolled in an introductory biomechanics course at a university, in Rio de Janeiro, Brazil, participated in this study. Meaningful learning theory was the major theoretical framework used in the study and content analysis of students’ learning activities were performed. Findings suggest that these students’ prior knowledge of functional anatomy was insufficient, fragmented, or missing, and these weaknesses in prerequisite knowledge and their approach to learning can be barriers to meaningful learning of biomechanical concepts.